Primary Hepatocellular carcinoma: management and prognosis - Murtaza Mustafa; HM. Iftikar; Firdaus Hayati; Em. Illzam; AM. Sharifa (International Organization of Scientific Research (IOSR), 2016)
Hepatocellular carcinoma (HCC) causes high mortality worldwide with 50 per cent of them in China. HCC cases are as a result of a viral hepatitis (hepatitis B or hepatitis C), metabolic toxins such as alcohol or aflatoxin, conditions like hemochromatosis and alpha 1-antitrypsin deficiency or non-alcoholic steatohepatitis (NASH). The high prevalence rate of hepatitis C virus (HCV occurs in African and Asian countries. The markers of hepatitis C infection (positive-anti HCV) are found in 80% - 90% patients in Japan, 70% in Egypt, 40- 50% in Pakistan and 35-40% in Saudi Arabia. China is classified as high endemic area with 8% - 20 % prevalence of hepatitis B virus (HBV). Other Asian countries are characterized as moderate to high prevalence rate of HBV in their population. The prevalence of HBV infection in children has declined in countries since the beginning of the vaccination. Chronic infections of hepatitis B and/or C can aid the development of HCC by repeatedly causing body’s immune system to attack the liver cells, some of which are infected by the virus. Aflatoxin is a carcinogen and aids carcinogenesis of HCC in the liver. Ultrasound and imaging modalities are used to aid in the diagnosis. Therapies include surgical resection, interventional radiology, and liver transplant. Prognosis for metastatic or unresectable HCC has improved due to sorafenib (Nexavar ®). Prevention of hepatitis B or C infection, childhood vaccination, reduce alcohol intake and avoiding the risk factors is the key to prevent HCC.